The Data Integration Research Group at UFPE - Salgado, Ana Carolina; Loscio, Bernadette F.; Batista, Maria da Conceição M.; Belian, Rosalie B.; Pires, Carlos Eduardo S.; Souza, Damires (Journal of Information and Data Management, 2011)
<!– /* Font Definitions */ @font-face font-family:Cambria; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:-536870145 1073743103 0 0 415 0; @font-face font-family:"MS ??"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"MS Mincho"; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:1 134676480 16 0 131072 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:Cambria; mso-fareast-font-family:"MS ??"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; font-family:Cambria; mso-ascii-font-family:Cambria; mso-fareast-font-family:"MS ??"; mso-hansi-font-family:Cambria; @page WordSection1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.WordSection1 page:WordSection1; –> One of the major database research areas is Data Integration, which refers to providing users with a uniform view over a set of heterogeneous, distributed and autonomous data sources. Data Integration settings concern, for instance, mediator-based integration systems and P2P ones (named Peer Data Management Systems). In these settings, users pose their queries without having to spend time in searching the set of distributed data sources individually. To help matters, research on Data Integration environments has considered the use of semantic knowledge in the form of ontologies and contextual information. For instance, ontologies can be used to solve the heterogeneities between the data sources, while contextual information allows the system to deal with information that is dynamically acquired during the execution of a given query. In this sense, the goal of this paper is to present the Data Integration on Dynamic Environments Group, focusing our discussions on its two main research areas: Mediation-based data integration and P2P data management.